2020
DOI: 10.3389/fpsyg.2020.579412
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Between Mothers and Fieldworkers While Assessing Child Development Using Ages and Stages Questionnaires, Third Edition in Nepal

Abstract: Background: The Ages and Stages Questionnaires, Third Edition (ASQ-3) is becoming a widely used developmental assessment tool. The ASQ-3 can be completed by the caregivers (referred to as “mail out”), or by trained personnel under direct observation of the children (referred to as “home procedure”). Aim: The study was carried out to compare results obtained by the ASQ mail out with those of the ASQ home procedure in a community setting of Bhaktapur, Nepal. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The ASQ-3 subscale contains 30 items divided into five developmental domains (six items per domain): communication, gross movement, fine movement, problem solving, and personal-social. Each item is rated to a score of 0, 5, and 10, with a total score for each domain of ASQ-3 ranging from 0 to 60 scores ( 15 ). There is also a comprehensive question section, which is about the concerns that parents may have about their children.…”
Section: Methodsmentioning
confidence: 99%
“…The ASQ-3 subscale contains 30 items divided into five developmental domains (six items per domain): communication, gross movement, fine movement, problem solving, and personal-social. Each item is rated to a score of 0, 5, and 10, with a total score for each domain of ASQ-3 ranging from 0 to 60 scores ( 15 ). There is also a comprehensive question section, which is about the concerns that parents may have about their children.…”
Section: Methodsmentioning
confidence: 99%
“…However, enumerators' capacity to apply psychometric tools with quality and reliability could be a potential reason for data quality. Some studies report poor agreement between parent and assessor scores on ASQ 3 (Shrestha et al, 2020). In fact, the Jensen et al study reported no bene ts with a direct assessment measure (Malawi Development Assessment Tool).…”
Section: Discussionmentioning
confidence: 99%
“…58 One advantage of the ASQ is that it can either be assessed directly by a trained examiners or answered by caregivers. 56,57 In this study, we used both approaches, prioritizing observations by trained examiners over caregiver response. A score of 10 was assigned if the child was observed/reported to “always” practice the behavior, 5 if the child sometimes practiced the behavior, and 0 if the child could not/did not practice it.…”
Section: Methodsmentioning
confidence: 99%
“…38,39,[51][52][53][54] Feasibility and construct validity in northern India 55,56 as well as in Nepal have recently been reported. 54,57 The test is scored by observation (or parent report) and consists of 30 age-specific items within 5 domains: communication (eg, at age 30 months, correctly naming pictures of items such as a ball, a hat), gross motor (able to jump with both feet leaving the ground at the same time), fine motor (able to string beads), problem-solving (identifying his/ her image in a mirror), and personal-social skills (able to put on a jacket or shirt independently). The instrument was translated and backtranslated from English to Nepali, minor changes were made to adapt to local conditions, and pilottested for clarity.…”
Section: Child Developmental Assessmentmentioning
confidence: 99%